Efeito da altura do remanescente coronário, do tipo de reconstrução interna e do tipo de coroa restauradora na deformação e resistência à fratura de dentes anteriores tratados endodonticamente - Silva, Natércia Rezende da (2008)
The endodontically treated teeth restoration is important aspect in dental practice and involves many treatment options with varying complexity. The aim of this study was to evaluate the strain, fracture resistance and failure mode of endodontically treated teeth depending of the post and core type, the ferrule presence, restored with metallic or ceramics reinforced with alumina crowns. 180 bovine incisors root were endodontically treated, divided into 2 groups (n = 90), prepared with ferrule (Fe) and without ferrule (NFe). Each group was divided into 3 subgroups (n = 30). The teeth were reconstructed with NiCr cast post and core (MFN); glass fiber post tapered smooth (PFv) and composite resin core and glass fiber post associated with fiber glass reforcore (PFvRc). Half of the samples (n = 15) of each subgroup has been restored with metallic crowns (Cm) and the other half restored with alumina ceramic (Cc). Compressive static load test was performed in 5 specimens to the load of 100N to measure the strain on the buccal and mesial root surfaces followed by continuous loading to failure (crack without complete fracture) in all specimens. Data were analyzed using 3 way-ANOVA and Tukey test (p =. 05). The failure mode was classified into 5 categories, based on the degree of damage to the structure and dental restorative procedure. Statistical analysis showed that the fracture resistance and buccal and proximal strain are influenced by factors and their interactions. The ferrule factor did not significantly influence the values of fracture resistance and buccal strain for groups Cc independent of the post and core reconstruction. The Cm associated with Fe results in significantly lower strain and higher fracture resistance that to NFe, regardless of the type of system post and core reconstruction. NMF showed significantly lower strain that PFv and PFvRc when employed metallic crown. In the ferrule presence, the post and core reconstruction system did not reflect in a significant difference in biomechanical behaviour independent of the crown type. The FeCm groups produced fractures involving the radicular coronary and medial third on other hand in NFeCm groups predominated fractures involving the core and radicular coronary third. The Cc groups have similar failure mode distribution. The biomechanical behavior of endodontically treated teeth restored with Cc independent of the post and core reconstruction type. The ferrule presence improves the mechanical behavior of the teeth restored with Cm independent of the post and core reconstruction type. In the ferrule absence the interaction of MFN with Cm resulted in better biomechanical performance.